Pemberdayaan Ekonomi Masyarakat Melalui Industri Bakpia di Desa Gembleb Kecamatan Pogalan Kabupaten Trenggalek - Indah Ainus Sofa; Mayda Putri Ardini; Elysia Septi Amanda; Isyfa Qurrata Aini; Surur Fatma Ningtyas; Ferdiaz Riandra Febriliant; Sandy Yudha Anggara Lhoksa; Bintis Ti'anatud Diniati (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
Community economic empowerment is a concept of economic development that contains social values, aiming to create a healthy and fair competitive climate. In Gembleb Village, empowerment is carried out through community participation in the bakpia industry. This activity aims to analyze the impact of economic empowerment through the bakpia industry on the community of Gembleb Village, Pogalan District, Trenggalek Regency. The bakpia industry is believed to have great potential in improving the welfare of the local community through job creation, income enhancement, and skill development. The objectives of this activity include: (1) identifying the contribution of the bakpia industry in creating job opportunities, (2) analyzing its impact on increasing income and economic welfare of the community, and (3) revealing the supporting and inhibiting factors in the development of the bakpia industry. This activity uses a qualitative approach with a case study method. Data were collected through observations, interviews with bakpia industry owners and practitioners as well as the community, and documentation. This activity found various factors that influence the development of the bakpia industry and its impact on economic empowerment. The findings are expected to provide strategic input for local governments, industry players, and related parties in developing a local economy based on village potential.